Safety of Lawn & Garden Products - Devlin, Daniel L.; Cress, Donald C.; Tisserat, Ned; Bauernfiend, Robert (My University, 1997)
This publication explains safe practices for using chemicals and other supplies on a lawn or garden.
MF2279_1997_07
Keywords: MF2279; Lawn and Garden; Environment and Natural Resources; MF